Aviation and healthcare: a comparative review with implications for patient safety. (2nd December 2015) - Kapur, Narinder; Parand, Anam; Soukup, Tayana; Reader, Tom; Sevdalis, Nick
Safety in aviation has often been compared with safety in healthcare. Following a recent article in this journal, the UK government set up an Independent Patient Safety Investigation Service, to emulate a similar well-established body in aviation. On the basis of a detailed review of relevant publications that examine patient safety in the context of aviation practice, we have drawn up a table of comparative features and a conceptual framework for patient safety. Convergence and divergence of safety-related behaviours across aviation and healthcare were derived and documented. Key safety-related domains that emerged included Checklists, Training, Crew Resource Management, Sterile Cockpit, Investigation and Reporting of Incidents and Organisational Culture. We conclude that whilst healthcare has much to learn from aviation in certain key domains, the transfer of lessons from aviation to healthcare needs to be nuanced, with the specific characteristics and needs of healthcare borne in mind. On the basis of this review, it is recommended that healthcare should emulate aviation in its resourcing of staff who specialise in human factors and related psychological aspects of patient safety and staff wellbeing. Professional and post-qualification staff training could specifically include Cognitive Bias Avoidance Training, as this appears to play a key part in many errors relating to patient safety and staff wellbeing.